An archivist in turbulent times: the activity of Áurea Javierre in the Library of the University of Zaragoza during the Spanish Civil War (1936- 1939) - Blanco Domingo, Luis (Revista General de Información y Documentación, 2019)
The objective of this article is to analyze the trajectory, accidental and transitory, of Áurea Javierre in the University Library of Zaragoza; during the Spanish Civil War (1936-1939). Through various documentary sources, a part of the biography of the turolense archivist virtually unknown is reconstructed, centered on her work organizing the Servicio de Lecturas del Soldado and her collaboration with Javier Lasso de la Vega, Head of Servicio de Archivos, Bibliotecas y Registro de la Propiedad Intelectual, in the adaptation of the Cuerpo Facultativo de Archiveros, Bibliotecarios y Arqueólogos to the new administrative structure that arose with the New State.